ظاهرة تسويق المواشي الجزائرية في أسواق الإيالة التونسية - زهيرة, سحابات (جامعة الوادي - University of Eloued, 2023)
يدور موضوع الدراسة حول:" ظاهرة تسويق المواشي الجزائرية في أسواق الإيالة التونسية خلال النصف الثاني من القرن 18م على ضوء وثائق أرشيفية تونسية "، حيث شكل النشاط التجاري الجزائري في تونس بمختلف أصنافه موردا اقتصاديا هاما لها خلال هذه الفترة ، وخاصة بعد انتشار هذه الظاهرة وهي تسويق الماشية الجزائرية في الأسواق التونسية وهي تجارة تخص الحكام بالدرجة الاولى ومما سهل عملية التسويق هذه هو وجود وكلاء جزائريون بتونس ساهموا في تفعيل هذه الحركية التجارية من خلال سعيهم في توزيعها على القواد وبيعها في أسواق مواطن الإيالة، وكانت عملية البيع تعتمد على صيغتين إما البيع المباشر أو البيع بالطلوق أي المؤجل، وتكون عملية البيع هذه محكمة في تقييدات يذكر بها عدد المواشي وصنفها مع السعر الذي بيعت به والذي يكون قد حدده حكام الجزائر أو بايات قسنطينة مسبقا مع عدم التساهل في المعاملات التجارية وخاصة قضية الدين، وإن كانت هذه الإمتيازات الإقتصادية المقدمة ماهي إلا نتاج انتصار سياسي وعسكري. Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article).Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article). Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article).Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article). The subject of the study concerns: “The phenomenon of the marketing of Algerian cattle on Tunisian markets during the second half of the 18th century AD in the light of Tunisian archival documents, resource for her during this period, especially after the spread of this phenomenon which is the marketing of Algerian cattle on Tunisian markets, which is a trade that belongs to the rulers in the first place, What has facilitated this process of marketing is the presence of Algerian livestock agents in Tunisia who helped to activate this commercial movement through their efforts to distribute them to pimps and sell them in the markets of the citizens of the province, and the process of sale was based on two forms either direct sale or deferred sale , number of cattle and their classification with the price at which they were sold, which may have been fixed by the rulers of Algeria or the bays of Constantine in advance, without leniency in commercial transactions. , in particular the question of the debt, although these granted economic privileges are only the product of a political and military victory.
خلال النصف الثاني من القرن 18م على ضوء وثائق أرشيفية تونسية
مقال
Keywords: الجزائر؛ تونس؛ التجارة ؛ المواشي؛ البيع; Algeria; Tunis; Trade; cattle; sale